2003
DOI: 10.1093/treephys/23.5.325
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing red expression in autumn foliage of sugar maple trees

Abstract: We evaluated factors influencing the development of autumn red coloration in leaves of sugar maple (Acer saccharum Marsh.) by measuring mineral nutrient and carbohydrate concentrations, water content, and phenology of color development of leaves from 16 mature open-grown trees on 12 dates from June through October 1999. Mean foliar nutrient and carbohydrate concentrations and water content were generally within the range published for healthy sugar maple trees. However, foliar nitrogen (N) concentrations were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
88
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(96 citation statements)
references
References 45 publications
8
88
0
Order By: Relevance
“…The results indicated that both studied traits were significantly affected by the environment. This might be due to the environmental factors such as UV-A, UV-B, temperature, light intensity, nutrition and moisture regulated the synthesis of anthocyanin in leaves (LEE et al, 2003;SCHABERG et al, 2003;TOSSI et al, 2011;WANG et al, 2012). In addition, highly significant difference between generations on the traits were detected, especially between parental lines (Figure 1).…”
Section: Resultsmentioning
confidence: 98%
“…The results indicated that both studied traits were significantly affected by the environment. This might be due to the environmental factors such as UV-A, UV-B, temperature, light intensity, nutrition and moisture regulated the synthesis of anthocyanin in leaves (LEE et al, 2003;SCHABERG et al, 2003;TOSSI et al, 2011;WANG et al, 2012). In addition, highly significant difference between generations on the traits were detected, especially between parental lines (Figure 1).…”
Section: Resultsmentioning
confidence: 98%
“…This is often confused with the following statement: that the trees with red leaves are the most vigorous ones. This misunderstanding has created much confusion, and because there is some evidence that weak trees often display strong autumn colours (Schaberg et al, 2003;Ougham et al, 2005), it may seem to undermine the coevolution theory.…”
Section: The Coevolution Theorymentioning
confidence: 99%
“…There is some evidence that the extent and earliness of onset of red coloration is positively correlated with foliar nitrogen deficiency in some cases (Schaberg et al, 2003;Ougham et al, 2005): this suggests that in these cases it is the weak trees that…”
mentioning
confidence: 99%
“…For example, Ishikura (1976) found an increase in total and reducing sugars followed by anthocyanin formation during autumnal senescence of leaves in three genera (Acer, Rhus, and Euonymous), whereas Chang et al (1989) noted that increases in glucose and galactose were coupled with red color development in senescing quaking aspen (Populus tremuloides) leaves. Schaberg et al (2003) also showed a significant and positive correlation between red coloration and sugar concentrations in senescing sugar maple leaves.…”
Section: Discussionmentioning
confidence: 80%
“…Research has linked the expression of anthocyanins to an assortment of environmental stresses, including drought (Zhang et al 2007), exposure to ozone and ultraviolet radiation (Alexieva et al 2001;Gravano et al 2004), wounding (Jeannette et al 2000;Gould et al 2002), bacterial and insect attacks (Gonzáles et al 2002;Edwards et al 2008), and nutrient deficiencies (Schaberg et al 2003). One of the most notable displays of foliar anthocyanin production occurs in autumn within deciduous temperate forests and coincides with the onset of low temperatures (Feild et al 2001;Schaberg et al 2003). Likewise, observations of anthocyanin production have been observed in the young foliage of some temperate species exposed to low temperatures in spring (Taulavuori et al 2011).…”
Section: Introductionmentioning
confidence: 99%